Arsenic–nucleotides interactions: an experimental and computational investigation. Issue 19 (25th April 2020) - Cassone, Giuseppe; Chillè, Donatella; Mollica Nardo, Viviana; Giuffrè, Ottavia; Ponterio, Rosina Celeste; Sponer, Jiri; Trusso, Sebastiano; Saija, Franz; Foti, Claudia
Abstract : By means of state-of-the-art computational approaches and experiments we characterize the chelation process established by As(iii ) with AMP, ADP, and ATP in aqueous solutions. Abstract : Albeit arsenic As(iii ) is a well-known carcinogenic contaminant, the modalities by which it interacts with living organisms are still elusive. Details pertaining to the binding properties of As(iii ) by common nucleotides such as AMP, ADP and ATP are indeed mostly unknown. Here we present an investigation, conducted via experimental and quantum-based computational approaches, on the stability of the complexes formed by arsenic with those nucleotides. By means of potentiometric and calorimetric measurements, the relative stability of AMP, ADP and ATP has been evaluated as a function of the pH. It turns out that ATP forms more stable structures with As(iii ) than ADP which, in turn, better chelates arsenic than AMP. Such a stability sequestration capability of arsenic (ATP > ADP > AMP) has been interpreted on a twofold basis via state-of-the-art ab initio molecular dynamics (AIMD) and metadynamics (MetD) simulations performed on aqueous solutions of As(iii ) chelated by AMP and ATP. In fact, we demonstrate that ATP offers a larger number of effective binding sites than AMP, thus indicating a higher statistical probability for chelating arsenic. Moreover, an evaluation of the free energy associated with the interactions that As(iii ) establishes with the nucleotide atoms responsible for the binding quantitatively proves the greater effectiveness of ATP as a chelating agent.